Evaluación del control interno en la constructora “Aguifierr S.A.” y su incidencia en la gestión administrativa año 2014 - Guerrero Purcachi, Karina Alexandra (2015)
The research was conducted in AguiFierr Construction SA, which is legally constituted in the Super Company, having as main activity the construction of civil works; it is located in the streets: Abdon. Calderon S / N Interception Street Atahualpa no. s / n. opposite the gas station windows Massur Canton province of Los Rios. The evaluation of internal control and its impact on the administrative management of the construction AguiFierr SA, the procedures and methods and research techniques such as interviews, surveys, questionnaire COSO internal control of the manager, the population of the applied company staff who is involved in this process of study, the sample and its population is finite and twenty people that work was not carried out, the confidence level was determined with a 56.69% and 43.31% risk negatively affecting company management. Because it lacks a strategic direction, lacks view, mission, long-term objectives, strategies and policies, which does not allow you to have a strategic planning that contributes to sustainable growth, in terms the functional organic structure, the company lacks, user functions, manual process and organizational chart which clearly defines the responsibilities and hierarchical levels. This does not allow the company to enjoy organized activities, which could represent losses for the company. Applying the COSO report assessing through the five components led us to obtain results as findings, they helped us draw conclusions, recommendations to prepare and submit the final report of the independent auditor